Knowledge Level of Women Dairy Farmers on Dairy Animal Management in Guntur District of Andhra Pradesh (Indian Journal of Animal Production and Management, 2024)
An investigation was undertaken to study  knowledge level of women dairy farmers on dairy  animal management in Guntur district of Andhra  Pradesh. A total of 225 randomly selected women  dairy farmers in three animal husbandry divisions of  Guntur district in Andhra Pradesh viz., Pedaravuru,  Guntur and Narasaraopeta. The farm women in the  study area had good knowledge regarding  importance of Artificial Insemination (96.40%), followed by identifying the animals in estrus  (95.10%), importance of treatment of anestrus and  repeat breeding animals (92.90%), culling of  unproductive animals (87.10%) and pregnancy  diagnosis at 3 months after insemination (86.70%).  Poor knowledge was observed regarding dry period  (20.90%), feeding concentrates according to the  level of production (16.00%), strip cup test to detect  mastitis (13.78%), urea treatment of paddy straw  (4.90%) and practicing of dry cow therapy (4.89%)  in the study area.
Keywords: dairy farming; farm women; Guntur; knowledge